3-D atomic-scale experimental and modelling studies of the early stages of precipitation - Cerezo, A; Hirosawa, S; Sha, G; Smith, G (2005)
The 3-dimensional atom probe (3DAP) permits the nanochemistry of metallic alloys to be observed with near-atomic spatial resolution and in 3 dimensions. This instrument is especially powerful for studying the early stages of diffusional phase trans format ions. By combining 3DAP analysis with 3-D Kinetic Monte Carlo (KMC) simulations, it is possible to compare directly the atomic-scale observations with atomistic modelling of the diffusion processes occuring during ageing over realistic timescales. This paper describes combined 3DAP analysis and KMC simulations of copper precipitation in pressure-vessel steels. and early-stage clustering in a 7050 (Al-Zn-Mg-Cu) alloy. 3DAP characterisation showed that clusters containing Ni and Mn were present in the steel prior to Cu precipitation. In the Al alloy. larger GP zones of composition Zn/Mg=1 were observed co-existing with smaller eta' platelets. the latter having formed from smaller GP zones. Despite the complexity of these engineering alloys, the KMC simulation was found to provide an accurate prediction of precipitate formation. and also correctly reproduced some of the more detailed aspects of alloy behaviour. The simulation also provided a tool for investigating the behaviour of the alloy in ways that are not possible experimentally. For example, the pre-existing clusters of Mn and Ni are seen to provide cluster-assisted nucleation of the Cu precipitates. This shows how ternary and higher-order additions can have profound influence on micro-structural development in an alloy, in ways that cannot be predicted from binary alloy behaviour, and that a combination of 3-D atomic-scale experiments and modelling are needed to understand fully these effects.